Framing Tirto.id Pada Pemberitaan Isu Kekerasan Seksual di Perguruan Tinggi - Damasemil, Calvin; Pradipta, Ade Devia (Institut Komunikasi dan Bisnis LSPR, 2023)
Sexual and gender-based violence is common all around us, even in college settings. From 2015 to 2021, there were 35 reports of sexual violence in college entering the Women's Chamber. The high rate of sexual abuse in college education, impacted on the publication of Permendikbud No. 30 Year 2021 on Prevention and Suppression of Sexual Violence in College. One of the most serious online media outlets reporting on cases of sexual violence in colleges is Tirto.id. Through Pan & Kosicki's analysis of the news, Tirto.id's position on college sexual assault groups tends to be biased on victims because Tirto is also advocating victims. Tirto.id doesn't dramatize by not giving a flattering opinion, but by providing chronology and facts on the victim's side. Tirto.id also continues to advance the presumption of innocence of the perpetrator because of his case which is still under investigation. Keywords: Framing Analysis, Sexual Violence, College, Online Media, Tirto.id.